Addressing a global epidemic: Opportunities for adult education to assist suicide loss survivors - Gina C. Whalen (Adult Education Research Conference, 2020)
Globally 800,000 people die by suicide every year. The worldwide prevalence of suicide has led to an increase in suicide prevention educational programming, but suicide bereavement education is rarely addressed. The upward trend of suicide rates has direct implications at the personal, community, societal, and global levels. The purpose of this literature review is to bring together empirical studies of those bereaved by suicide from various fields, so that researchers in adult education have a direction for this much-needed area of exploration. Three themes emerged during this research: (a) unique bereavement challenges, (b) barriers to obtaining support, and (c) sources of effective support. The studies were conducted in the fields of death and dying, mental health, public health, nursing, and suicidology with only one study conducted in the field of adult education. The results of this literature review can serve as a starting point for synergistic endeavors between adult education researchers and scholars in these fields to create programing that will serve the needs of suicide loss survivors. Such endeavors will bridge the gap between adult education theories and praxis.
Keywords: Suicide bereavement; suicide loss survivors; adult education